Targeting toll-like receptor-4 (TLR4)—an emerging therapeutic target for persistent pain states. Issue 10 (October 2018) - Bruno, Kelly; Woller, Sarah A.; Miller, Yury I.; Yaksh, Tony L.; Wallace, Mark; Beaton, Graham; Chakravarthy, Krishnan
Abstract : Abstract: Toll-like receptors (TLRs) are a family of pattern recognition receptors that initiate signaling in innate and adaptive immune pathways. The highly conserved family of transmembrane proteins comprises an extracellular domain that recognizes exogenous and endogenous danger molecules and an ectodomain that activates downstream pathways in response. Recent studies suggest that continuous activation or dysregulation of TLR signaling may contribute to chronic disease states. The receptor is located not only on inflammatory cells (meningeal and peripheral macrophages) but on neuraxial glia (microglia and astrocytes), Schwann cells, fibroblasts, dorsal root ganglia, and dorsal horn neurons. Procedures blocking TLR functionality have shown pronounced effects on pain behavior otherwise observed in models of chronic inflammation and nerve injury. This review addresses the role of TLR4 as an emerging therapeutic target for the evolution of persistent pain and its role in noncanonical signaling, mediating anomalous pro-algesic actions of opiates. Accordingly, molecules targeting inhibition of this receptor have promise as disease-modifying and opioid-sparing alternatives for persistent pain states.